The determinants of global bank lending: Evidence from bilateral cross-country data - Aysun, Uluc; Hepp, Ralf (Journal of Banking & Finance, 2016)
This paper finds that factors determined outside of a country, at the quarterly frequency and especially after 2008, are more closely related to the global bank loans it receives. These loans are generally more stable when global banks face more competition and have a higher presence in the recipient country. We obtain our results by using bilateral lending data from 15 countries and a unique methodology to identify and compare the independent effects of external and internal factors. We identify theoretical mechanisms that can explain our empirical findings and draw more detailed inferences for competition and global bank presence by solving a simple model of global banking.